“We Might Get Some Free Beers”: Experience and Motivation for Transactional Sex Among Behaviorally Bisexual Men in Vientiane, Laos - Bowring, A.; Pasomsouk, N.; Hughes, C.; van Gemert, C.; Higgs, Peter; Sychareun, V.; Hellard, M.; Power, R. (Springer New York LLC, 2016)
People engaging in transactional sex are considered a key population for HIV prevention. Prior quantitative surveys demonstrated that behaviorally bisexual men in Vientiane, Laos commonly transact sex. In 2013, we conducted a qualitative study to explore behaviorally bisexual men’s experience, motivations, and perceptions related to transactional sex in Vientiane. Behaviorally bisexual men were recruited from bars, nightclubs, and dormitories for five focus group discussions (FGDs) and 11 in-depth interviews (n = 31). Additionally, young women were recruited from a university, garment factory, and nightclub for four FGDs (n = 22). Transcripts were translated and thematically coded. Bisexual male participants most commonly described being paid for sex by male-to-female transgender people and buying sex from women. Both male and female participants reported that older, single women pay younger men for sex. Negotiation and direction of sexual transactions are influenced by age, attraction, and wealth. Common motivations for selling sex included the need for money to support family or fund school fees, material gain, or physical pleasure. Transactional sex was often opportunistic. Some behaviorally bisexual men reported selling sex in order to pay another more desirable sex partner or to buy gifts for their regular sex partner. Participants perceived high risk associated with intercourse with female sex workers but not with other transactional sex partners. Health interventions are needed to improve knowledge, risk perception, and health behaviors, but must recognize the diversity of transactional sex in Vientiane. Both physical and virtual settings may be appropriate for reaching behaviorally bisexual men and their partners.